Sistem Pakar Diagnosa Kerusakan Dan Perawatan Laptop - Sadly, Muhammad; Dani, Ahmad Ali Hakam; Abduh, Hisma (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Expert System for diagnosing laptop damage and maintenance is an information and communication system that arises to provide solutions to a problem related to the laptop itself. This system is designed using the backward chaining method with the first dept technique as its inference engine, black box as a testing system, Microsoft access 2007 as the database and visual basic 6.0 as the programming language. Data collection was carried out for three months using interview and observation methods which were located at Central Media Computer. This research resulted in an expert system to provide information on symptoms, diagnoses and solutions to laptop damage and in the usability aspect based on testing using the Computer System Usability Questionnare produced a total score of 1538 which was converted on an index scale to a value of 85.4% included in the